Calculation of Propulsive Motion for Two-Jointed Bionic Robotic Dolphin - Zhiqun Yuan; Yuxuan Chang; Chen Chen; Yanqiang Chen; Shuixuan Chen (Applied Bionics and Biomechanics)
The cruising propulsion process of the bionic robotic fish under the swinging tail motion presents a strong periodic dynamic response, and accurate prediction of its performance is the key to the overall design. Taking the two-jointed bionic robotic dolphin as the research object, five kinds of movement modes were designed, and the coupled analysis model of the propulsion motion of the bionic robotic dolphin was established based on the hydrodynamic and Lagrangian dynamics methods, and the hydrodynamic performance of different movement modes and its linear propulsion dynamic response process were investigated. The results show that the coupled analysis method proposed in the paper can accurately obtain the motion response parameters of the robotic dolphin as well as the forces and moments of each joint, and the speed error with the hydrodynamic simulation is controlled within 5%. The research method and results have good application value to guide the selection design and performance prediction of bionic robotic fish.